Relationship between the vertical distribution of fine roots and residual soil nitrogen along a gradient of hardwood mixture in a conifer plantation - Morikawa, Yumena (The New phytologist, 2022)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.